حديث - التضييق على أهل الكتاب في الطريق: دراسة عقدية - حمزة، علي أبو الفتح حسين Hamzah, Ali Abu Alfath Hussein (جامعة النيلين - كلية الدراسات العليا, 2018)
A Hadith said that the Messenger of Allah peace and blessings be upon him ordered his followers to narrow the pass way of the people of the book- Jews and Christians – it is very significant to elaborate on the meaning of this Hadith ( tradition) in order to demonstrate the scientific method adopted by the Messenger peace be upon him and his companions after him and what the Muslims that come after them should adopt when dealing with the non-Muslim minorities living in the Muslim countries , following the moderate approach of Islam which sets it apart from other approaches because of not being harsh and extreme when it comes to rights and duties .the researcher followed the inductive analytical methodology in tackling issues of this tradition explaining its meaning , the ways it was narrated , and how authentic it is , these supported with the views of the scholars and jurists of Islamic Sharia and the explainers of prophetic traditions and explain the conditions set by them to apply the tradition in reality , those restrictions and conditions include that the application of it is subject to the state of Muslim nation being strong and no harm will happen to the people of the book . From the study it became clear that the tradition is authentic and is binding, because it was narrated in most of the books of Sunnah, the application of the tradition in reality requires understanding the restrictions and conditions mentioned by the jurists in order to prevent aggression and injustice. Establishing the meaning of this tradition does not contradict with other texts commanding Muslims to be kind to the people of the book because those texts are general while the meaning of this Hadith is particular. It was clear from the study that the relationships among people and the consideration of their rights should be referred to the impeccable revelation and not the desires and moods of people. When we do not refer to the texts of revelation would lead to contradiction and may be hatred and wars. It is also important in this regard to demonstrate the need to show rights and establish them and to show the tolerance and to consolidate self-esteem and morale of the followers of Islam.
قد ورد عن رسول الله صلى الله عليه وسلم حديث يأمر بتضييق الطريق على أهل الكتاب من اليهود والنصارى، وكشف معنى هذا الحديث وتوضيحه ذو أهمية عظيمة في بيان المنهج العلمي الذي سار عليه رسول الله صلى الله عليه وسلم وأصحابه من بعده وما ينبغي أن يسير عليه المسلمون بعدهم في التعامل مع الأقليات غير المسلمة التي تقيم في البلاد الإسلامية. متبعين في ذلك منهج وسطية الإسلام الذي يميزه عن غيره من المناهج بعدم الجفاء والغلو في ما يتعلق بالحقوق والواجبات، وقد اتبع الباحث في هذا الموضوع منهج البحث العلمي بالسير على المنهج الاستقرائي التحليلي في معالجة قضايا هذا الحديث مبينًا لمعناه وطرقه ودرجته من القبول معضدًا ذلك بأقوال علماء الإسلام وفقهاء الشريعة وشراح الحديث، وبيان ما وضعوا له من شروط لتحقيقه وتطبيقه، والتي منها أن هذا الحديث محمول على حالة قوة المسلمين ومنعتهم، وعدم وقوع الضرر بأهل الكتاب، وقد تبين من هذه الدراسة صحة الحديث المشار إليه والاحتجاج به، وأنه مخرج في أكثر كتب السنة ودواوينها المسندة، وأن تطبيق هذا الحديث في الواقع يحتاج إلى أعمال واستصحاب الشروط التي ذكرها الفقهاء حتى لا يؤدي الأمر إلى تعدي وظلم، وأن تقرير معنى هذا الحديث لا يتعارض مع النصوص الآمرة بالإحسان إلى أهل الكتاب لأنها نصوص عامة، ودلالة الحديث خاصة، كما تبين أن العلاقة بين الناس واعتبار حقوقهم ينبغي أن يكون المرجع فيها الوحي المعصوم لا ما يراه الناس من أهوائهم وأمزجتهم لأن ترك الرجوع إلى نصوص الوحي يوقع في التناقض بل ربما البغضاء والاحتراب، ومن المهم في هذا الصدد أن هذا البحث يقرر ضرورة بيان الحقوق وإشاعتها واظهار سماحة الإسلام وعزته، ورفع الروح المعنوية لأتباعه.
Keywords: الشريعة الإسلامية -- أهل الكتاب -- أهل الذمة -- آداب السلام